PERBANDINGAN EFEK PERASAN LIDAH BUAYA (Aloe vera L.) DENGAN Povidone Iodine 10% TERHADAP JUMLAH SEL NEUTROFIL DARAH dan JARINGAN KULIT LUKA SAYAT PUNGGUNG TIKUS WISTAR JANTAN - Vahda Bara Nanda Avisha (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2019)
Introduction: The active substance lupeol, beta-cystosterol, campesterol in Aloe vera L. helps in the wound healing process by increasing anti-inflammation which causes a decrease in the number of blood neutrophil cells and tissue neutrophils. However, studies that prove that the active ingredient in the extract of Aloe vera L. can help the wound healing process is still rare.Method: This study was an experimental in vivo control group post test only design laboratory. This study used male Wistar rats aged 2-3 months were divided into 5 sample groups; treatment group 0 group (K0), negative group(KN), treatment group 1(P1), treatment group 2(P2) and treatment group 3(P3). Rats were given a wound of 2cm and 0,2mm deep. Rat positive group was given Povidone Iodine 10% ,treatment group 1 was given a dose of Aloe vera L juice 20%, treatment 2 at a dose of 40%, and treatment 3 with a dose of 80% given for 6 days, day 7 was performed for sampling. The number of blood neutrophils counted by Differential Count, the number of tissue neutrophils is calculated under a microscope with 400x magnification. Data analysis using One Way ANOVA (p <0.05).Results: The 80% dose of Aloe vera L. tended to reduce the number of neutrophil cells even though it was not significant, while the number of tissue neutrophils in the back wound of male wistar rats decreased significantly by 50% compared to K0 (p <0, 05).Conclusion: The juice of Aloe vera L. has the potential to accelerate the wound healing process by reducing the number of blood neutrophil cells and the number of neutrophil cells in skin tissueKeywords: Wounds, Wound healing, Positive substances of Aloe vera L., Number of neutrophil blood cells and tissues